THE ROLE OF OPTICAL COHERENCE TOMOGRAPHY IN THE EARLY DETECTION OF GLAUCOMA AND AGE-RELATED MACULAR DEGENERATION (Modern American Journal of Medical and Health Sciences, 2026)
Optical coherence tomography (OCT) is a modern, non-invasive diagnostic modality in ophthalmology that enables high-resolution cross-sectional imaging of ocular tissues. This article provides a comprehensive analysis of the role of OCT in the early detection of glaucoma and age-related macular degeneration (AMD), highlighting its capabilities, advantages, and clinical significance.